2001
DOI: 10.1034/j.1399-0039.2001.057005457.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I genotyping including HLA‐B*51 allele typing in the Iranian patients with Behçet’s disease

Abstract: It is well known that Behçet's disease (BD) is strongly associated with human leukocyte antigen (HLA) B51 in many ethnic groups. However, there has been no published report as yet with respect to this association among the Iranian people. Furthermore, since it is now known that the B51 antigen can be encoded by 21 alleles, B*5101-B*5121, we performed HLA-B*51 allele typing as well as HLA class I genotyping of 48 Iranian patients with this disease. As a result, the frequency of the B*51 allele was significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
(12 reference statements)
1
32
4
Order By: Relevance
“…Members of this group share the amino acid alanine at position 26, which contributes to the structure of peptide-binding pocket B and determines the motif of bound peptides [16]. In this study, we found three HLA-B alleles different from others studies in which the HLA-B * 51 allele has been associated consistently in Turkish, Korean, Greek, Japanese, Israel Arabs, Iranian, Italian, and Moroccan patients [17][18][19][20][21][22][23][24]. These alleles, in Mexicans, might be the equivalent of HLA-B51 found in the above mentioned populations.…”
Section: Discussioncontrasting
confidence: 46%
“…Members of this group share the amino acid alanine at position 26, which contributes to the structure of peptide-binding pocket B and determines the motif of bound peptides [16]. In this study, we found three HLA-B alleles different from others studies in which the HLA-B * 51 allele has been associated consistently in Turkish, Korean, Greek, Japanese, Israel Arabs, Iranian, Italian, and Moroccan patients [17][18][19][20][21][22][23][24]. These alleles, in Mexicans, might be the equivalent of HLA-B51 found in the above mentioned populations.…”
Section: Discussioncontrasting
confidence: 46%
“…While HLA-A*26 has been reported to be associated with BD in Taiwan and in Greece [39,40], no significant associations have been found between HLA-A alleles and BD in studies conducted in Palestine, Jordan, Iran, Ireland, Italy, or Turkey [29,[41][42][43][44]. However, it was clearly demonstrated that HLA-A*26 is a primary susceptibility gene of BD in the Japanese GWAS [11].…”
Section: Hla-a Regionmentioning
confidence: 54%
“…HLA-B*5101 allele expression is associated with Behçet disease [31,32], a multisystemic inflammatory disorder possibly of autoimmune nature [33,34]. The linkage is very suggestive of involvement of peptide presentation function, since Behçet disease is not associated with HLA-B*5201, which differs by only two amino acids located in the pocket B of the peptidebinding groove [34].…”
Section: Discussionmentioning
confidence: 84%